Caesarean scar pregnancy in the UK: a national cohort study - Harb, H; Knight, M; Bottomley, C; Overton, C; Tobias, A; Gallos, I; Shehmar, M; Farquharson, R; Horne, A; Latthe, P; Edi-Osagie, E; MacLean, M; et al. (Wiley, 2018)
To estimate the incidence of caesarean scar pregnancy (CSP) and to describe the management outcomes associated with this condition DESIGN: A national cohort study using the UK Early Pregnancy Surveillance Service (UKEPSS).86 participating Early Pregnancy Units.All women diagnosed in the participating units with CSP between November 2013 and January 2015.COHORT STUDY OF WOMEN IDENTIFIED THROUGH THE UKEPSS MONTHLY MAILING SYSTEM: MAIN OUTCOME MEASURES: Incidence, clinical outcomes and complications.102 cases of CSP were reported, with an estimated incidence of 1.5 per 10,000 (95% CI 1.1 - 1.9) maternities. Full outcome data were available for 92 women. Management was expectant in 21/92 (23%), medical in 15/92 (16%), and surgical in 56/92 (61%). The success rates of expectant, medical, and surgical management were 43% (9/21), 46% (7/15) and 96% (54/56) respectively. The complication rates were 15/21 (71%) with expectant, 9/15 (60%) with medical and 20/56 (36%) with surgical management. Discharge from care (median number of days) was 82 (range 37-174) with expectant, 21 (range 10-31) with medical, and 11 (range 4-49) with surgical management.Surgical management appears to be associated with a high success rate, low complication rate and short post-treatment follow up. This article is protected by copyright. All rights reserved.